The Concretization of Criminal Sanctions by Judges to Support Corruption Eradication - Maria Grasia Sari Soetopo (GoAcademica Research & Publishing, 2023)
The criminal act of corruption is a crime that has long been known to mankind. Various efforts in Indonesia have been carried out to increase the effectiveness of corruption eradication. Such support is demonstrated by the Supreme Court through the issuance of Supreme Court Regulation Number 1 of 2020 concerning Sentencing Guidelines for Article 2 and Article 3 of the Eradication of Corruption Crimes Law (Perma No. 1 of 2020). However, this regulation lacks concrete formulation of criminal sanctions and insight of corruption impacts on society. The aim of this research is to analyze approaches for judges in concretizing their considerations when imposing criminal sanctions to support the eradication of corruption. This research was prepared using normative legal research methods and supported by descriptive economic analysis. The result of this study shows the need for improvements to Perma No. 1 of 2020 by focusing the impacts of corruption on legal developments in society. These efforts, moreover, need to be supported by reviewing the range of criminal sanctions contained in the provisions of Article 2 and Article 3 of the Law concerning the Eradication of Corruption Crimes, as well as Article 603 and Article 604 of Law Number 1 of 2023 concerning the Criminal Code.